The rights and well-being of children of incarcerated parents in Estonia - Strömpl, Judit (European Integration Studies, 2024)
This article provides an overview of the situation of children of incarcerated parents (IP) in Estonia compared to the international situation from the perspective of the rights and well-being of the child. Studies published in recent years focus on the negative impact of parental imprisonment on the well-being of their children and on child resilience (i.e. how children cope with this difficult situation). Legal regulation seeks to provide a framework to safeguard the child’s well-being considering the child’s rights. Drawing on relational-culture theory, this article addresses the issue of parental imprisonment from the perspective of the relationships between the different actors involved – the child, the IP, other carers outside the prison, the community, and society. Legal regulation seeks to standardise these relationships at international and national levels. The international legislation (United Nations Convention on the Rights of the Child, Charter of Fundamental Rights of the European Union, Council of Europe on European Prison Rules) is designed to protect the rights and well-being of the child, and it must be considered in all situations worldwide, including when a parent is serving a prison sentence. The main question of this article is how does Estonian legislation, child protection policy, and practice meet international requirements for children of detained parents? Using a case-study method, the article introduces the current situation in the Estonian prison system in terms of conditions for communication between children with their IPs. The relevant Estonian laws (Constitution of the Estonian Republic, Family Law Act, Child Protection Act, Prison Act, Prison Rules) are analysed in the article in comparison to international legislation and their practical implementation.